How much public spending does each area receive? Local authority level estimates of health, police, school and local government spending - Kate Ogden; David Phillips; Max Warner (Institute for Fiscal Studies (IFS), 2023)
How much funding does each area of England receive for key public services, and is this funding allocated in line with patterns of needs?
Keywords: 330; Government finances and spending; Geography; Government spending; Inequality; Local government finance; NHS; Public finance; Schools